2021
DOI: 10.1111/tmi.13568
|View full text |Cite
|
Sign up to set email alerts
|

Health and social outcomes of HIV‐vulnerable and HIV‐positive pregnant and post‐partum adolescents and infants enrolled in a home visiting team programme in Kenya

Abstract: objectives HIV-positive and HIV-vulnerable pregnant adolescent girls and adolescent mothers face significant barriers and vulnerabilities. Infants born to adolescent mothers are also more likely to die and be exposed to life-threatening conditions. This paper presents findings from an evaluation of a programme that used a home visitation model and offered a case-management, team-focused approach to increase family and community supportiveness to enhance health and social service uptake among pregnant adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Suggestions to enhance the wellbeing of pregnant women included income support, life skills training, maternal mental health care, treatment for harmful substance use, and home visits which were thought to have potential benefits for the children as well. While the study did not focus on pregnant and parenting adolescent girls, the findings align with the perspectives of policymaker informants from this study and with adolescents from our other study arm and other studies in Kenya [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
“…Suggestions to enhance the wellbeing of pregnant women included income support, life skills training, maternal mental health care, treatment for harmful substance use, and home visits which were thought to have potential benefits for the children as well. While the study did not focus on pregnant and parenting adolescent girls, the findings align with the perspectives of policymaker informants from this study and with adolescents from our other study arm and other studies in Kenya [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
“…Among these, age, education levels and marital status were the most controlled for. Three studies in an article by Morgan and colleagues ( 29 ) and one study in an article by Levy and colleagues ( 30 ) identified PROGRESS-Plus factors, but failed to include them in their final analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As expected with non-RCTs, most studies 76.9% ( n = 20) included were labelled as moderate risk studies across all domains. Five studies were labelled as serious risk studies across all domains ( 30 , 38 41 ) and one study by Fikree and colleagues ( 42 ) was judged to be critical risk of bias study.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that PCC strategies have the potential to overcome inequities in access to HIV services, support quality care that is responsive to diverse needs while increasing efficiencies and resilience of the health system. [7] Practical examples of PCC within the context of HIV treatment available in the literature, including differentiated treatment delivery models, adolescent-friendly services, workplace interventions and peer-led support, have demonstrated that PCC can improve treatment outcomes across the care continuum [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%